2014
DOI: 10.3892/mmr.2014.2232
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor γ agonist rosiglitazone inhibits migration and invasion of prostate cancer cells through inhibition of the CXCR4/CXCL12 axis

Abstract: It has been indicated that the C‑X‑C chemokine receptor type 4/C‑X‑C chemokine ligand 12 (CXCR4/CXCL12) axis is involved in promoting invasion and metastasis in tumors. Therefore, novel drugs capable of downregulating the CXCR4/CXCL12 axis may demonstrate potential for the treatment of metastatic prostate cancer (PCa). Rosiglitazone (RSG), a thiazolidinedione ligand of the peroxisome proliferator‑activated receptor (PPAR) γ, has been found to inhibit proliferation, induce apoptosis, suppress angiogenesis and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Previous studies have proposed that activation of PPARγ by RGZ inhibits growth of various types of cancer [2022]. To verify the inhibitory effect of activation of PPARγ on esophageal cancer cells, EC109 and TE10 cells were treated with 0, 10, 20, and 40 μM of RGZ for 24, 48, and 72 h, and proliferation of EC109 and TE10 cells were determined using MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have proposed that activation of PPARγ by RGZ inhibits growth of various types of cancer [2022]. To verify the inhibitory effect of activation of PPARγ on esophageal cancer cells, EC109 and TE10 cells were treated with 0, 10, 20, and 40 μM of RGZ for 24, 48, and 72 h, and proliferation of EC109 and TE10 cells were determined using MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…Certain previous studies have reported that PPARγ is able to induce anti-proliferative, anti-angiogenic and pro-differentiation signaling pathways in specific tissue types, thus serving a role in the pathogenesis and progression of various types of cancer, including prostate cancer (24,25). Using TZDs as PPARγ ligands, previous studies have investigated the effect of PPARγ on the metastatic potential and investigated its underlying mechanisms (26)(27)(28)(29)(30)(31)(32)(33)(34). TZDs have been demonstrated to be able to suppress cellular migration, invasion and metastasis of cancer in the colon, liver, breast, lung, bladder and prostate gland (26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Using TZDs as PPARγ ligands, previous studies have investigated the effect of PPARγ on the metastatic potential and investigated its underlying mechanisms (26)(27)(28)(29)(30)(31)(32)(33)(34). TZDs have been demonstrated to be able to suppress cellular migration, invasion and metastasis of cancer in the colon, liver, breast, lung, bladder and prostate gland (26)(27)(28)(29)(30)(31)(32)(33)(34). For example, in colon cancer, TZD inhibited the development and metastasis of HT-29 human colon cancer cells via its differentiation-promoting effects both in vivo and in vitro by involving the modulation of the E-cadherin/β-catenin system (26).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it has been reported that in prostate cancer tissue, PPARs can promote the upregulation of VEGF thus enhancing tumour vascularisation and growth (Haslmayer et al 2002, Forootan et al 2016. This is quite in conflict with in vitro work and another report which suggests that PPARs inhibit vascularisation (Qin et al 2014), thus further work is needed to elaborate the beneficial or harmful role of PPARs in prostate cancer development and progression.…”
Section: Peroxisome Proliferator-activated Receptors (Ppars or Nr1c1/mentioning
confidence: 93%
“…PPARs can mediate apoptosis and proliferation as well as prostate cancer cell differentiation (Koeffler 2003, Nagata et al 2008, Wu et al 2016b. PPARs have also been reported to alter prostate cancer motility by regulating the CXCR4/CXCL12 axis (Qin et al 2014). The action of PPAR also has benefit in increasing response to chemotherapy, as treating with PPAR ligands appears to increase apoptosis (Koeffler 2003).…”
Section: Peroxisome Proliferator-activated Receptors (Ppars or Nr1c1/mentioning
confidence: 99%